2010
DOI: 10.1111/j.1462-5822.2010.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis employs Cpn60.2 as an adhesin that binds CD43 on the macrophage surface

Abstract: SummaryCD43 is a large sialylated glycoprotein found on the surface of haematopoietic cells and has been previously shown to be necessary for efficient macrophage binding and immunological responsiveness to Mycobacterium tuberculosis. Using capsular material from M. tuberculosis and recombinant CD43-Fc, we have employed affinity chromatography to show that Cpn60.2 (Hsp65, GroEL), and to a lesser extent DnaK (Hsp70), bind to CD43. Competitive inhibition using recombinant protein and polyclonal F(abЈ) 2 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 54 publications
(99 reference statements)
2
44
0
Order By: Relevance
“…CD43 may bind specifically to Mycobacteria but not to other types of bacteria (18,19,29). Moreover, Hickey and colleagues described the MTB molecular chaperone Cpn60.2 as a mycobacterial surface ligand that interacts with CD43 to stabilize the interaction between the mycobacteria and the macrophage (30). CD43 has also been shown to regulate intracellular MTB growth and TNF secretion (19), reducing TNF secretion in response to infection and shifting macrophage's cell death away from apoptosis to necrosis (20).…”
Section: Clinical Relevancementioning
confidence: 99%
“…CD43 may bind specifically to Mycobacteria but not to other types of bacteria (18,19,29). Moreover, Hickey and colleagues described the MTB molecular chaperone Cpn60.2 as a mycobacterial surface ligand that interacts with CD43 to stabilize the interaction between the mycobacteria and the macrophage (30). CD43 has also been shown to regulate intracellular MTB growth and TNF secretion (19), reducing TNF secretion in response to infection and shifting macrophage's cell death away from apoptosis to necrosis (20).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Bacterial GroEL heat shock proteins are a conserved group of chaperonins whose function to mediate protein folding has made them widely essential to resist various stressors such as extreme temperatures or nutrient limitation (164,265,348). Interestingly, although no member of the GroEL family bears any discernible secretion signal, overwhelming evidence indicates that surface-exposed or secreted GroEL plays a key role in the infection strategies of many bacterial pathogens (35,181,184; reviewed in reference 174). As an example, the corresponding homolog of Legionella pneumophila is known to be displayed on the bacterial surface, where it promotes an invasive phenotype, and the same protein apparently manipulates cellular trafficking, cytoskeleton, and signaling once it is released inside the eukaryotic host cell (recently reviewed in reference 153).…”
Section: The Primary Nichementioning
confidence: 99%
“…Despite high sequence similarity to other chaperonins, functional studies on GroEL2 initially identified it as the immunodominant antigen in the mycobacterial culture filtrates, leading to the search for its immunological roles (Lamb et al 1989;Cehovin et al 2010;Henderson et al 2010Henderson et al , 2013. Therefore, studies that followed focused on understanding the immunological tasks of the Mtb GroELs, which eventually demonstrated that all the chaperonins, GroEL1 (Lewthwaite et al 2001), GroEL2 (Hickey et al 2010), and GroES (Sonnenberg and Belisle 1997), are secreted, with GroEL1 being the more immunopotent (Lewthwaite et al 2001). Immunological function is driven by a polypeptide segment in the equatorial domain of GroEL1 (Hu et al 2013).…”
Section: Multiple Groels In Mycobacteriamentioning
confidence: 99%